Umlagerungen bizyklischer 2-Vinyl-aziridine - Lienhard Hoesch; André S. Dreiding (CHIMIA)
Addition of phthalimidonitrene to cyclopentadiene (5), 1,3-cyclohexadiene (6) as well as cyclooctatetraene (7) led to the bicyclic 2-vinyl-aziridines: N-phthalimido-6-aza-bicyclo[3.1.0]hex-2-ene (8a), N-phthalimido-7-aza-bicyclo[4.1.0]hept-2-ene (9a) and N-phthalimido-9-aza-bicyclo[6.1.0]nona-2,4,6-triene (10a), respectively. Thermolysis of 8a gave pyridine (16) and phthalimide (17), whereas from the thermolysis of 9a and of 10a the products of a 2-vinylaziridine-rearrangement were isolated, namely N-phthalimido-7-aza-bicyclo[2.2.1]hept-2-ene (11) and N-phthalimido-9-aza-bicyclo[4.2.1]nona-2,4,7-triene (23), respectively. 11 was found to be thermally labile under the conditions of its formation and decomposed into N-phthalimido-pyrrole (12) and, presumably, ethylene. N-Phthalimido-indole (24) was isolated as a by-product from the thermolysis of 10a.